2023
DOI: 10.1101/2023.05.30.542725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptic architecture of leg and wing premotor control networks inDrosophila

Abstract: Animal movement is controlled by motor neurons (MNs), which project out of the central nervous system to activate muscles. Because individual muscles may be used in many different behaviors, MN activity must be flexibly coordinated by dedicated premotor circuitry, the organization of which remains largely unknown. Here, we use comprehensive reconstruction of neuron anatomy and synaptic connectivity from volumetric electron microscopy (i.e., connectomics) to analyze the wiring logic of motor circuits controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 159 publications
0
33
0
Order By: Relevance
“…This NeuroAI approach is enabled with unprecedented spatial and temporal detail by our body model and imitation learning framework. Future work can leverage the connectomic mapping of the entire fruit fly nervous system , Lesser et al, 2023, Azevedo et al, 2022, Takemura et al, 2023 to more realistically model neural circuits underlying sensorimotor behavior. In the short term, our body model and imitation learning framework can enable the model-based investigation of the neural underpinnings of sensory-motor behaviors such as escape invoked by looming stimuli [Card, 2012], gaze-stabilization [Cruz and Chiappe, 2023], the control of movement by the ventral nerve cord [Lesser et al, 2023, Azevedo et al, 2022, Takemura et al, 2023.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This NeuroAI approach is enabled with unprecedented spatial and temporal detail by our body model and imitation learning framework. Future work can leverage the connectomic mapping of the entire fruit fly nervous system , Lesser et al, 2023, Azevedo et al, 2022, Takemura et al, 2023 to more realistically model neural circuits underlying sensorimotor behavior. In the short term, our body model and imitation learning framework can enable the model-based investigation of the neural underpinnings of sensory-motor behaviors such as escape invoked by looming stimuli [Card, 2012], gaze-stabilization [Cruz and Chiappe, 2023], the control of movement by the ventral nerve cord [Lesser et al, 2023, Azevedo et al, 2022, Takemura et al, 2023.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, new imaging of musculature and sensory systems can improve biomechanical fidelity of actuation and sensory feedback. The black-box artificial neural network controllers we trained using imitation learning can be made more realistic by introducing connectome constraints [Lappalainen et al, 2023] based on recent measurements of connectivity of the brain and ventral nerve cord [Lesser et al, 2023, Azevedo et al, 2022, Takemura et al, 2023, as well as neural activity , Pacheco et al, 2021, Aimon et al, 2023. Thus our present work serves as a platform to enable future studies of embodied cognition [Zador et al, 2023], modeling the neural and biomechanical basis of sensorimotor behavior in unprecedented detail.…”
Section: Introductionmentioning
confidence: 99%
“…At present, connectomic analysis is also typically limited to very small sample sizes, usually just one, and so we cannot address variability both within and between species. These limitations will eventually be overcome through advances in electron (Cheong et al, 2023;Dorkenwald et al;Lesser et al, 2023;Marin et al, 2023;Phelps et al, 2021b;Scheffer et al, 2020;Schlegel et al, 2023a) and light (Lillvis et al, 2022) microscopy to provide molecular detail and to allow study of much larger sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Split-GAL4 enhancer combinations identified in D. melanogaster have been used to target pIP10 in D. yakuba (Ding et al, 2019), suggesting that the split-GAL4 reagents we have identified may be useful for studying homologous circuits across Drosophila species. Testing anatomical hypotheses will require comparative connectomics, which should be facilitated by recent advances in EM (Dorkenwald et al;Lesser et al, 2023;Marin et al, 2023;Phelps et al, 2021a;Scheffer et al, 2020;Schlegel et al, 2023aSchlegel et al, , 2023bSheridan et al, 2022;Xu et al, 2017) and in expansion microscopy (Lillvis et al, 2022).…”
Section: Song Evolutionmentioning
confidence: 99%
See 1 more Smart Citation